Quasi-experimental Clinical Trial on the Efficacy of In-house Collected Eggshell Membrane for the Management of Osteoarthritis - Myint Swe; Abdul Karim Russ Hassan; Wahinuddin Sulaiman; Ramachandran Vignesh; Nor Aini Abdullah (Asian Journal of Medicine & Health Sciences, 2023)
Glucosamine products are widely used for the treatment of osteoarthritis (OA). Eggshell membrane (ESM) is a natural source of glucosamine, collagen, and hyaluronic acid, which are essential for cartilage health. ESM also possesses anti-inflammatory and immunomodulatory properties, that can help reduce pain and improve joint function in OA patients. This is a singlearm quasi-experimental clinical trial to determine the efficacy of in-house collected ESM in the management of OA. We prepared the ESM from eggshells, pasteurized it to eliminate bacterial contamination, and then packed it as a capsule containing 250 mg of ESM per capsule. This study involved fifty-four participants with OA who met the eligibility criteria. They received two capsules of ESM daily for 30 days as a treatment. We used a questionnaire with a visual analogue scale (VAS) to measure their pain and stiffness levels at baseline and on the 10th, 30th, 60th, and 90th day after commencement of the treatment. The Friedman and post-hoc pairwise comparison Conover tests were used to test the significant reduction of the pain score. A P-value of 0.05 was taken as the significant limit. Of the fifty-four voluntary participants who enrolled in the study, three dropped out, resulting in a response rate of 94.4%. This study found that treatment with ESM significantly reduced pain scores for all 10 symptoms on day 30 compared to the initial baseline (P < 0.01). This improvement remained consistent on days 60 and 90 (P>0.05). Only one participant (1.9%) reported a ’warm sensation,’ and no other adverse effects were reported. Inhouse collected ESM is a safe and effective alternative to glucosamine products for the management of OA. It can provide relief from pain and stiffness and improve joint function in OA patients.